Electro-pulse method for obtaining raw materials for subsequent flotation enrichment of ore - Khassenov, A.K.; Stoev, M.; Karabekova, D.Zh.; Bulkairova, G.A.; Nurbalayeva, D.А. (KU Publ., 2021)
The main method of enrichment of polymetallic ores is flotation. The peculiarity of solid mineral processing is the preliminary preparation of raw materials. The essence of this stage is the grinding and sorting of raw materials in order to fully reveal the useful substance from the waste rock. The article is devoted to the study of the effect of electric pulse discharges on the grinding of ore containing non-ferrous metals. This article proposes an electro-pulse method for obtaining raw materials for subsequent flotation enrichment of ore in order to extract valuable components. This method of grinding ores is based on the use of the energy of a pulsed shock wave that occurs as a result of a spark electric discharge in a liquid. An experimental electric pulse unit with a crushing unit is described. When electrohydraulic action on solid particles in an aqueous solution increases the intensity of the grinding process under the influence of additional pressure associated with cavitation. The object of the study was the natural ore of the Akbastau mine. Ore grinding operations were performed at various parameters of the electric pulse plant. The dependences of ore grinding on the electrical and geometric parameters of the electric pulse installation, the value of the interelectrode gap on the switching device, the pulse repetition frequency and discharge energies are determined. It is found that with increasing discharge energies introduced into the discharge channel, the fraction of the crushed fraction increases.
Кенді флотациялық байытуға қажетті шикізатты алудың электримульсті əдісі
Электроимпульсный метод получения сырья для последующего флотационного обогащения руды
Keywords: ore; flotation; electric pulse installation; working electrode; degree of grinding; crushing; discharge energy